The Role of Goods Importation in Supporting the Economy: A Literature Review Study - Susanto, Primadi Candra; Perwitasari, Erni Pratiwi; Lermatan, Esterlinus Edwin (Siber Journal of Transportation and Logistics, 2025)
This study aims to formulate a comprehensive theory regarding the role of importation in the national economy. In the context of globalization and free trade, imports have become vital instruments supporting a country’s economic activities. This article presents a literature review highlighting the contribution of import activities to economic growth, referring to academic sources, policy reports, and empirical data. The study emphasizes several key benefits of imports, such as fulfilling domestic market needs, improving production efficiency, and gaining access to new technologies. On the other hand, the review also identifies challenges associated with imports, such as increasing dependency on foreign products and potential threats to the sustainability of local industries. Using a descriptive-qualitative approach, this review seeks to provide a comprehensive understanding of import dynamics and their implications for national economic development. The findings of this study are expected to serve as valuable input for formulating sustainable and competitive trade policies.